Occupational accident due to exposure to biological material in the nurses - Guimarães Ximenes Neto Rosemiro, Francisco Rosemiro (2022)
Objective: To describe the epidemiology of occupational accidents with exposure to biological material among nurses. Method: Epidemiological, descriptive and retrospective study, involving 102 cases of occupational accidents among nurses. Results: There was a predominance of females (77.4 %); 20 to 29 years of age (58.8 %); and brown skin color (53.9 %). Most of the workers had a work registration (64.7 %). In 68.2% of the cases, the circumstance of the accident was percutaneous exposure and, in 71.5%, by organic material - blood; the main agent was the lumen needle (66.6 %); 44.1 % were wearing gloves and 35.9 % were wearing masks at the time of the accident; (43.2 %) had the case evolution field filled in as ignored/white. Conclusion: Accidents are mostly the result of daily practice actions, such as punctures, although these professionals use protective equipment. Therefore, continuing education on safety at work, coupled with awareness about the relevance of notification is a challenge for the exercise of a safe practice.